Molecular epidemiology of Salmonella Infantis in Europe: insights into the success of the bacterial host and its parasitic pESI-like megaplasmid. Issue 5 (9th May 2020) - Alba, Patricia; Leekitcharoenphon, Pimlapas; Carfora, Virginia; Amoruso, Roberta; Cordaro, Gessica; Di Matteo, Paola; Ianzano, Angela; Iurescia, Manuela; Diaconu, Elena L.; Study Group, ENGAGE-EURL-AR Network; Pedersen, Susanne K.; Guerra, Beatriz; et al.
Abstract : Salmonella Infantis is one of the five serovars most frequently causing human salmonellosis in Europe, mainly associated with poultry. A clone harbouring a conjugative plasmid of emerging S . Infantis (pESI)-like megaplasmid, carrying multidrug resistant (MDR) and extended-spectrum beta-lactamases (ESBL) genes, has spread in the Italian broiler chicken industry also causing human illness. This work is aimed at elucidating the molecular epidemiology of S . Infantis and pESI-like in Europe using whole-genome sequencing and bioinformatics analysis, and to investigate the genetic relatedness of S . Infantis clones and pESI-like from animals, meat, feed and humans provided by institutions of nine European countries. Two genotyping approaches were used: chromosome or plasmid SNP-based analysis and the minimum spanning tree (MST) algorithm based on core-genome multilocus sequence typing (cgMLST). The European S . Infantis population appeared heterogeneous, with different genetic clusters defined at core-genome level. However, pESI-like variants present in 64.1 % of the isolates were more genetically homogeneous and capable of infecting different clonal lineages in most of the countries. Two different pESI-like with ESBL genes ( n =82) were observed: bla CTX-M-1 -positive in European isolates and bla CTX-M-65 -positive in American isolates (study outgroup). Both variants had toxin-antitoxin systems, resistance genes towards tetracyclines, trimethoprim, sulphonamides and aminoglycosides, heavy metals ( mer A) and disinfectants ( qac EΔ). Worryingly, 66 % of the total isolates studied presented different gyr A chromosomal point mutations associated with (fluoro)quinolone resistance (MIC range 0.125–0.5 mg/L), while 18 % displayed transferable macrolide resistance mediated by mph, mef and erm (B) genes. Proper intervention strategies are needed to prevent further dissemination/transmission of MDR S . Infantis and pESI-like along the food chain in Europe.